Cross-cultural adaptation and psychometric properties of the Thai version of the Neurophysiology of Pain Questionnaire in individuals with chronic low back pain - Pasangkayo, Pichet; Jensen, Mark P.; Kanlayanaphotporn, Rotsalai; Janwantanakul, Prawit (Archives of Allied Health Sciences, 2022)
Pain neurophysiology knowledge is hypothesized to influence pain beliefs and physical performance in individuals with chronic low back pain (LBP). Valid and reliable measures of such knowledge are important to evaluate the pain treatment on this domain as well as to understand its role in both physical and psychological functions of individuals with chronic pain. This study aimed to culturally adapt the revised Neurophysiology of Pain Questionnaire into Thai (T-rNPQ), using the Functional Assessment of Chronic Illness Therapy translation methodology, and to evaluate its reliability and validity. Two hundred sixty-three individuals with chronic LBP completed the T-rNPQ and seven health and function domains of Thai versions of the Patient-Reported Outcomes Measurement Information System-29. Forty-five lecturers in musculoskeletal physical therapy completed the T-rNPQ. A subset of 95 individuals with chronic LBP completed the T-rNPQ again after an interval of seven to 15 days. Internal consistency for the total score and two subscales that emerged in the current analyses showed marked variability (Cronbach’s alphas = 0.82, 0.82, and 0.63). Test-retest reliability was poor to good (ICC’s(2,1) = 0.71, 0.40, and 0.65). Known-groups and discriminant construct validity of the T-rNPQ total score and subscale scores were satisfactory. The findings indicate that the T-rNPQ measures two knowledge domains, i.e., ‘Neurophysiology Knowledge’ and ‘Pain means Harm’. The psychometric property assessment of the T-rNPQ indicated that using the scale in Thai individuals with chronic LBP should be undertaken with discretion.